A camelid VHH-based fluorescence polarization immunoassay for the detection of tetrabromobisphenol A in water. Issue 39 (27th September 2016) - Wang, Kai; Liu, Zhiping; Ji, Pei; Liu, Jianfeng; Eremin, Sergei A.; Li, Qing X.; Li, Ji; Xu, Ting
Abstract : Tetrabromobisphenol A (TBBPA) is a widely used flame retardant and is classified as an endocrine disruptor. Abstract : Tetrabromobisphenol A (TBBPA) is a widely used flame retardant and is classified as an endocrine disruptor. A convenient and sensitive fluorescence polarization immunoassay (FPIA) for TBBPA was developed with a camelid variable domain of heavy chain antibody (VHH) being specific for TBBPA. 3-(2, 6-Dibromo-4-(2-(3, 5-dibromo-4-hydroxyphenyl)propan-2-yl))propanoic acid (hapten T1) was conjugated with ethylenediamine fluorescein thiocarbamoyl (EDF) to form a tracer that binds with anti-TBBPA VHH. The limit of detection and half-maximum inhibition concentration of TBBPA by FPIA were 5 ng mL −1 and 90 ng mL −1, respectively. This FPIA was used to detect TBBPA in water samples without any pre-treatment and each analysis was performed within 20–30 min. The recovery of TBBPA from spiked water samples ranged from 73% to 102%, with coefficients of variation ranging from 7% to 14%. The FPIA exhibited high potential for rapid and accurate determination of TBBPA in real water samples.